“Are you sure you want to go to that village”; a qualitative review of the challenges, experiences and lessons learnt from a nutritional survey in rural and urban communities in Nigeria - Adeleye Abiodun Adeomi (BMC Research Notes)
Abstract Introduction The importance of community-based studies is not in doubt, however only few exist because of the complexity and challenges associated with them. Little data exists on these complexities and challenges in West Africa. This study aimed to describe the experiences, challenges and lessons learnt from a community-based Nutritional survey carried out in Nigeria. This was a qualitative review of the experiences and challenges involved in a community-based research project. A thematic content analysis was done and the findings were presented as themes and sub-themes, with the inclusion of quotes that accurately depicted the themes/sub-themes. Results Two broad themes emerged from the study. For observations and experiences with community entry, sub-themes include the finding that community structure in the books were different from community structure on the ground, there was a general mistrust among community members, poor access to some communities and/or houses, there was a poor perception of need for the research, there was concern about risk to study participants and about benefit to the participants. The five sub-themes that pertained to the data collection process include the issues with timing, gender, data quality, men being at home and safety of the research team. Guided community engagements are recommended.